Uptake of Health Services by People from the Dalit Community - Thapa, Raksha; van Teijlingen, E.; Regmi, P.; Heaslip, V. (Journal of BP Koirala Institute of Health Sciences, 2018)
Studies and reports on uptake of health services in Nepal and other low-income countries often focus on limitations due to physical factors, such as travel distance to health facility, or lack of medical facilities or electricity at the health care centre or focus on resources, such as lack of service providers, or lack of appropriately trained staff.In this editorial article, we highlight the importance of discrimination as a reason for people not seeking available health care. Discrimination is particularly a barrier to service usage among the most deprived people in society, such as the Dalit community in Nepal and South Asia more generally. We discuss the caste-based discrimination in Nepal and its effects on health outcomes of those groups who experience such discrimination.